Analysis of the antimicrobial activity of the extract of the metapleural gland of Paraponera clavata (FABRICIUS,1775) (FORMICIDAE:PARAPONERINAE) (Research, Society and Development, 2021)
The resistance of pathogenic microorganisms to conventional drugs constitutes a serious Public Health problem. The problem of resistance has generated the need for knowledge of bioactive substances that can act as alternatives in the treatment of infections caused by fungi and bacteria. The antimicrobial effect of metapleural gland secretion has already been demonstrated in some species of ants. Therefore, the present study aimed to verify the antimicrobial effect of the extract of the metapleural gland of the ant Paraponera clavata against ATCC strains of pathogenic bacteria Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae and the fungus Candida albicans. of ants, which are kept in artificial nests. The metapleural glands were extracted and macerated in hexane, followed by solvent evaporation steps. Susceptibility tests were performed using the agar diffusion methodology in wells, with wells being formed in the second layer and 40µl of the metapleural gland extract sample were added. Different concentrations of the metapleural extract were tested against microorganisms. It was found that the extract from the metapleural gland of P. clavata did not inhibit the bacteria and fungus used in the research. However, the importance of carrying out tests with other microorganisms is highlighted, considering that the potential of the metapleural gland of other ant species has been proven in previous studies and the relevance of the discovery of alternative bioactive compounds.